Cholesterol Oxidase Binds TLR2 and Modulates Functional Responses of Human Macrophages - Bednarska, Katarzyna (Hindawi Publishing Corporation, 2014)
Cholesterol oxidase (ChoD) is considered to be an important virulence factor for Mycobacterium tuberculosis (Mtb), but its influence on macrophage activity is unknown. Here we used Nocardia erythropolis ChoD, which is very similar to the Mtb enzyme (70% identity at the amino-acid level), to evaluate the impact of bacterial ChoD on the activity of THP-1-derived macrophages in vitro. We found that ChoD decreased the surface expression of Toll-like receptor type 2 (TLR2) and complement receptor 3 (CR3) on these macrophages. Flow cytometry and confocal microscopy showed that ChoD competed with lipoteichoic acid for ligand binding sites on TLR2 but not on CR3, suggesting that ChoD signaling is mediated via TLR2. Binding of ChoD to the membrane of macrophages had diverse effects on the activity of macrophages, activating p38 mitogen activated kinase and stimulating production of a large amount of interleukin-10. Moreover, ChoD primed macrophages to enhance the production of reactive oxygen species in response to the phorbol myristate acetate, which was reduced by “switching off” TLR-derived signaling through interleukin-1 receptor-associated kinases 1 and 4 inhibition. Our study revealed that ChoD interacts directly with macrophages via TLR2 and influences the biological activity of macrophages during the development of the initial response to infection.